Privacy Preservation In The Digital Era In A Secure Documentation Policy Paradigm - Heri Tahir; Ririn Nurfaathirany Heri; Asri Ismail (Cita konsultindo, 2025)
The distribution of personal data is not only related to misuse of data in banking cases. Currently there are many posts on social media related to videos or photos of other people for the benefit of personal accounts, organizations or companies, as well as the distribution of documentation in social media groups without the consent of the person concerned, so that someone in the photo or video experiences a violation of their personal rights and right to privacy. Seeing the phenomenon of people who are still not fully aware of the personal rights and privacy rights of other people, it is very interesting to research related to maintaining privacy in the digital era.This research will be carried out using the Juridical-Normative research method, which has the character of a perspective or applied science, Legal Science as Sui Generis. Researchers use a statutory approach and a comparative approach.Awareness of the right to privacy and protection of personal data increases every year but is still relatively low when compared to electronic media users. The development of digital technology, social media, and the use of online platforms in everyday life has had a significant impact on people's understanding and awareness of the importance of protecting privacy and personal data. On the other hand, despite increasing awareness, there is still ignorance, a lack of understanding of the law, and a lack of attention to the potential risks of personal data breaches in the digital world. Factors that influence public awareness of the protection of privacy rights and personal data protection in Indonesia are the lack of understanding and education regarding digital literacy from the perspective of privacy rights and protection of personal rights.